Survival benefit of surgical resection for stage IV gastric cancer: A SEER-based propensity score-matched analysis - Sun, Jianhui; Nan, Qiong (Frontiers in Surgery, 2022)
Background: Gastric cancer (GC) is a major malignancy worldwide, and its incidence and mortality rate are increasing year by year. Clinical guidelines mainly use palliative drug combination therapy for stage IV gastric cancer. In accordance with some small sample studies, surgery can prolong survival. There is no uniform treatment plan for stage IV gastric cancer. This study focused on collecting evidence of the survival benefit of cancer-directed surgery (CDS) for patients with stage IV gastric cancer by analyzing data from a large sample. Methods: Data on patients with stage IV gastric cancer diagnosed between 2010 and 2015 was extracted and divided into CDS and no-CDS groups using the large dataset in the Surveillance, Epidemiology, and End Results (SEER) database, with bias between the two groups minimized by propensity score matching (PSM), the prognostic role of CDS was studied by the Cox proportional risk model and Kaplan-Meier. Results: A total of 6284 patients with stage IV gastric cancer were included, including 514 patients with CDS who were matched with no-CDS patients according to propensity score (1:1), resulting in the inclusion of 432 patients each in the CDS and no-CDS groups. The results showed that CDS appeared to prolong the median survival time for stage IV gastric cancer (from 6 months to 10 months). Multifactorial analysis showed that poorly differentiated tumors (grades III-IV) significantly affected patient survival, and chemotherapy was a protective prognostic factor. Conclusion: The findings support that CDS can provide a survival benefit for stage IV gastric cancer; however, a combination of age, underlying physical status, tumor histology, and metastatic status should be considered when making decisions about CDS, which will aid in clinical decision making.